LEGAL PROTECTION FOR REPORTERS OF DRUG CRIMES BASED ON LAW NUMBER 35 OF 2009 - Nadya Prameswari; Mhd. Azhali Siregar; Fitria Ramadhani (International Journal of Synergy in Law, Criminal, and Justice, 2024)
The participation of the community in helping law enforcement officials to prevent and eradicate narcotics abuse is expected to make a very large contribution, considering that the number of personnel of the apparatus itself is very minimal if it has to supervise the illicit circulation of narcotics in the territory of Indonesia which consists of thousands of islands. Based on the actions that will threaten the safety of the witness, it is necessary to have a guarantee of security and protection from the authorities. For this reason, without being asked for witnesses, the authorities must provide security guarantees and the best protection for witnesses if they later experience threats or intimidation from narcotics syndicates.